Open Grid Service Architecture (OGSA) SOA journey from web services to grid computing. - Abaas, Ramy
A service oriented architecture (SOA) is based on services that are self-describing and open components that can be used to build distributed applications. A service is implemented by a software module that responds to queries and commands by performing a specified function. There is a large degree of standardization in the operation of Web services.